Formula 1, city and tourism: a research theme analyzed on the basis of a systematic literature review. Issue 4 (15th June 2020) - Roult, Romain; Auger, Denis; Lafond, Marie-Pierre
Abstract : Purpose: This paper aims to draw up the state of scientific knowledge in the field of Formula 1 with relation to tourism and urban studies. Design/methodology/approach: This study is based on a systematic review of the scientific literature regarding this issue. Using targeted keywords and the analysis of various documentary databases, 8, 075 references were identified and 40 documents were analyzed in an exhaustive manner. Findings: This study presents a very nuanced portrait of the urban and tourism impacts of Formula 1 on the host territories. In many of the studies analyzed, a gap may be noted, sometimes flagrant, between the development goals of the promoters of these mega-events and local realities. This study also highlights the fact that Formula 1 has established itself as a sports events industry that can renew and enhance the brand image of certain cities. Originality/value: Very few recent studies have exhaustively reviewed the scientific literature published in English and French with regard to the field of Formula 1 from a tourism and urban perspective. This study makes it possible to identify the main analytical findings and research perspectives resulting from this scientific work while discussing them using a theoretical framework related to the hypermodern character of different societies.